The Effect of Counseling on Pregnant Women's Knowledge and Attitude Regarding Complication Prevention - Ismiati, Ismiati; Khairani, Fuji; Syuryani, Lili (GLOBAL HEALTH SCIENCE GROUP, 2024)
Pregnancy complications are health problems that occur during pregnancy. These health problems can involve problems with the mother's health, the baby's health or even both. Some pregnant women have health problems that arise during pregnancy, while there are also some women who have health problems before pregnancy which can lead to complications during pregnancy. Therefore, it is important for women to receive health care before and during pregnancy to reduce the risk of pregnancy complications. Objective: To determine the effect of counseling on the level of knowledge and attitudes of pregnant women regarding preventing complications in the Hu'u Poskesdes work area in 2023. Method: The design of this research is a pre-experimental design with a one group pretest-posttest design. The sample in this study was 33 pregnant women respondents. Sampling in this research was carried out using a probability sampling method, namely the random sampling technique providing equal opportunities for each element or member of the population to be selected as a sample. Data collection was carried out by filling out the pre-test and post-test questionnaires after a week of the pre-test, where before being given the post-test intervention was given in the form of counseling through lectures/slides.The analysis used is the Wilcoxon Signed Ranks Test analysis. Results: From the univariate results before providing education on preventing complications, it was in the good category (15.2%), sufficient (63.6%), poor (21.2%) and after providing education on preventing complications, it was in the good category (54.5%), sufficient. (42.4%), less (3.0%). Attitudes before were positive = 16 (48.5%) and negative = 17 (51.5%), while after attitudes were positive as many as 24 (72.7%) and negative as many as 9 (27.3%). Test the results of the Wilcoxon Signed Ranks Test analysis with a P-value of knowledge level of 0.01 P of 0.01<0.05 and P-value of attitudes of pregnant women of P=0.046 P of 0.046 <0.05. Conclusions: Counseling has an influence on the level of knowledge and attitudes of pregnant women regarding preventing complications in pregnancy.